Interpersonal Communication About Authoritarian Parenting Patterns in The Formation of Adolescent Self-Concept - Dewi, Devita Resti; Supratman, Lucy Pujasari (PT Mattawang Mediatama Solution, 2024)
This research examines how parents implement authoritarian parenting patterns and then shape adolescents' self-concept. Research uses qualitative methods with constructivist paradigms and case study approaches. Data was collected through unstructured interviews, non-participatory observations, and documentation of three mothers using authoritarian parenting as well as three teenagers receiving such parenting. Research findings suggest that maternal authoritarian parenting includes strict control, numerous bans, penalties, and lack of bargaining. These mothers implement strict discipline with the aim of forming disciplined, obedient, and independent adolescents. However, this parenting pattern is often a legacy of the way their parents raised themselves. This study found that authoritarian parenting can shape various aspects of adolescent self-concept. Teenagers can develop positive self-concepts such as time discipline and independence, but there is also a tendency to form negative self-concepts such as closed and rebellious. This study recommends that parents be more open and less restrictive to adolescents, so that they feel more free and closer to their parents. Rather than giving a prohibition, it is better for parents to make a choice with an explanation of the consequences of each choice. This will help teenagers to be more careful in making decisions. Further research on the topic of authoritarian parenting and adolescent self-concept is also highly recommended to expand understanding and knowledge in this field.